Exploring Concepts of Leadership and Leadership Development Within an International Development Through Sport Context - Olver, Denise (Université d'Ottawa / University of Ottawa, 2012)
Today’s youth are tomorrow’s leaders’, and for that reason, it is considered important by researchers and practitioners alike to understand how to develop effective leadership skills and characteristics. The purpose of this research was to explore concepts of leadership including leadership development (LD) within an international development through sport context. The Commonwealth Games Association of Canada’s (CGC) International Development through Sport (IDS) administration team created a program called the Capacity Support Program (CSP). The CSP is an internship program offered to recent university graduates to assist in various initiatives intended on building sporting capacity within partnering Commonwealth countries. Participants also known as Capacity Support Officer’s (CSO’s) were immersed within an international environment with a host sport organization (e.g., Barbados National Olympic Committee) for approximately fourteen-months. In this study, interviews were conducted with IDS administrators to clarify and provide further detailed information about the program. In addition, archival material (e.g., pre-departure training manual, website articles, DVDs), interviews with CSO’s, and a debrief focus group session with the CSO’s which discussed their experiences and the various concepts of leadership and LD within an international development through sport context was conducted. Data was recorded and transcribed verbatim. A grounded theory approach, specifically the inductive coding technique was utilized throughout the content analysis procedure. Findings showed that concepts of leadership and LD were 1) a fundamental component of the program and 2) linked to various existing literature on leadership theories (e.g., authentic leadership). Further, findings demonstrated the program design and training were significant components of LD and that the cross-cultural context accelerated LD. These findings and others will culminate in a discussion regarding future studies of leadership and LD.
Keywords: Leadership; Leadership Development; Development of Sport; Development through Sport; International Development; Organizational Development